Deciphering The Role Of Gga-Mir-142-3p On Target Gene Cd200 And Its Contribution Towards Signal Transduction And Immune Response (Applied Biological Research, 2017)
The gga-miR-142-3p is highly expressed during immune organ development and functional stages in chicken embryo. The present study was carried out to  explore the role of miR-142-3p and its importance in regulating the expression  of target gene CD200 involved in signal transduction and immune response.  Presence of binding site for miR-142-3p on 3’ UTR of CD200 gene was identified  by bioinformatics analysis. Real time qPCR analysis revealed significant  changes in the expression of CD200 gene in immune organs and other organs of  miRNA knockdown embryos compared to scramble control embryos.  Altogether, knockdown of gga-miR-142-3p in the chicken embryo resulted in  the over expression of CD200 in immune organs and visceral organs indicating  CD200 as a validate target of gga-miR-142-3p. This study suggests aberrant  expression of gga-miR-142-3p during the embryonic developmental stage may  lead to malfunctioning of the immune organs.
Keywords: CD200 expression; chicken embryo; gga-miR-142-3p; knock down